Preparations for the International specialized exhibition EXPO-2017: first results of the active participation of the regions of Kazakhstan - Syzdykova, E.Zh.; Abilov, D.K. (Ye.A.Buketov Karaganda State University Publ., 2014)
The article presents material on the relevance and importance of the International specialized exhibition EXPO-2017 in Astana, as well as on the activities conducted in the regions of the Republic of Kazakhstan to prepare for it. Content of the article speaks of the importance of EXPO-2017 in the social, economic and environmental development of the regions. The article notes that the main advantage of the International specialized exhibition EXPO-2017 in Astana for the regions are experience, advanced technology, jobs and scientific potential for the use of them in the implementation of the «green economy».
ЭКСПО-2017 Халықаралық арнайы көрмесіне дайындық: Қазақстан аймақтарының белсенді қатысуының алғашқы нəтижелері
Подготовка к Международной специализированной выставке ЭКСПО-2017: первые результаты активного участия регионов Казахстана
Keywords: International specialized exhibition; green economy; future energy; regions; advanced technology; obs and scientific potential